The conceptual model of personal moral philosophy (PMP) and ethical decision making (EDM) - Ling, Meng Chan; Othman, Jamilah; Joned, Rusinah (2011)
The purpose of this study is to develop a conceptual model to examine the two dimensions of personal moral philosophy (Idealism and Relativism) and its influences on the Ethical Decision Making. The study use the Forsyth’s Taxonomy of Personal Moral Philosophy and the Rest’s Ethical Decision Making Model serves as the starting points to develop the conceptual model. Two dimensions of PMP and 4 main components of EDM were used to construct the model from the extensive literature. The developed model will provide the base for assessing the level of EDM by studying the influences of the level of PMP. This finding further the insight of the understanding of the philosophical and ethical analysis of managerial dilemmas. The model provides an insightful for the analysis of PMP on EDM. The model examines the independent influences of PMP on EDM and treats EDM as dependent variables. Given that EDM are often detrimental to organizational functional efficiency, it is appropriate for the management to have betterunderstanding to diagnose effects of the PMP on the EDM. For this analysis, this model will prove valuable.